Analisis Gizi Limbah Ampas Kedelai Sebagai Tepung Subtitusi Mie untuk Menunjang Sumber Belajar Mata Kuliah Biokimia - Anggi Dwi Putri; Fatimatuz Zuhro; Ismul Mauludin Al Habib (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
Research this aim to know nutritional proximate analysis of okara noodle products that have the potential to add protein values and dietary fiber to noodles and whether this research can be used as a source of biochemistry learning resources. The initial stage of this research is the flouring okara followed by making wet noodle okara and analyze the nutritional content characterized by the high content of fiber and protein than wheat flour. The results showed that the nutritional value of wet noodles with okara flour substitution had 6.7% protein, ash 0.27%, water 66%, carbohydrate 26%, fat 0.5%, and fiber 2.4%. The content of okara noodle fiber is able to meet the sufficiency of fiber consumption recommended by United States Department of Agriculture (USDA) amount 25 - 30g for a day . Substitution of okara flour can significantly increase the value of protein and dietary fiber in wet noodles. Data of research result from nutrient analysis of okara noodles using proksimat method can also be used as supporting source of biochemistry course study Keywords : proximate test, okara noodles, waste, learning resources